2019
DOI: 10.21470/1678-9741-2018-0409
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Video-assisted Mitral Valve Replacement with a Right Chest Small Incision in Patients Aged Over 65 Years

Abstract: Objective To analyze and summarize the clinical safety and feasibility of minimally invasive video-assisted mitral valve replacement via a right thoracic minimal incision in patients aged over 65 years. Methods The clinical data of 45 patients over 65 years old who had mitral valve disease were analyzed retrospectively from January 2014 to January 2017 at Union Hospital, Fujian Medical University. The patients were divided into two groups; 20 patients in group A, who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The studies were relatively recent with the oldest study published in 2011 and the most recent one published in 2019. The smallest study reported on 45 patients 12 and the largest study reported on 340 patients. 16 All of the studies provided a comparison between elderly patients (≥65 years old) undergoing mitral valve surgery through a minimally invasive versus a sternotomy approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were relatively recent with the oldest study published in 2011 and the most recent one published in 2019. The smallest study reported on 45 patients 12 and the largest study reported on 340 patients. 16 All of the studies provided a comparison between elderly patients (≥65 years old) undergoing mitral valve surgery through a minimally invasive versus a sternotomy approach.…”
Section: Resultsmentioning
confidence: 99%
“…There were 10 retrospective observational cohort studies providing a head-to-head comparison between MIMVS and CS in elderly patients (≥65 years old), with a total of 1,897 patients (929 patients in the MIMVS group and 968 patients in the CS group). 4,6,[8][9][10][11][12][13][14][15][16] We had access to the full texts of 7 studies 4,6,[8][9][10][11][12] and only to the abstracts of 3 studies. [13][14][15][16] After reviewing these 3 abstracts along with their accompanying materials, it was believed that we had access to enough information to make an assessment of the quality of the studies and to extract the appropriate information for our systematic review and meta-analysis.…”
Section: Characteristics Of Included Studies and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SMR needs to split the sternum in the middle, which destroys the normal bone structure of the sternum and increases the pain experienced by the patient after operation. With the use of wire and bone wax, the risk of foreign body rejection is higher in SMR [Pradeep 2021;Chen 2019]. Additionally, obese patients or patients with diabetes are more prone to incision fat liquefaction or infection, resulting in a prolonged unhealed incision and leaving large scars [Peng 2019;Lv 2019].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive approaches are used in several clinical conditions such as functional mitral insufficiency, 5 endocarditis 6 with successful results. MICS is feasible also for the over‐65s and elderly 7 and for high‐risk patients 8 . In centers used an almost invisible suture line as surgical access is appealing, as well, especially in young women.…”
Section: Discussionmentioning
confidence: 99%